A59: Dexamethazone Therapy for Septic Arthritis in Children: a Follow Up Study. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Fogel, Itay; Amir, Jacob; Bar‐On, Elhanan; Harel, Liora
Abstract : Background/Purpose: In our previous prospective study we have demonstrated that the administration of Dexamethasone as an adjuvant therapy lead to a significant clinical and laboratory improvement in children with septic arthritis. This therapy has become accepted in some of the pediatric wards at Schneider's medical center. The aim of this study was to evaluate the effect of adding Dexamethasone to antibiotic therapy on the clinical course of septic arthritis in children not under controlled study. Methods: A retrospective study included all children hospitalized with the diagnosis of septic arthritis at Schneider Children's Medical Center from 2008–2013 .Part of the patients were treated with antibiotics alone, whereas others were treated with Dexametasone in addition to antibiotics, according to the policy of the admitting ward. Results: 116 medical records were included in our study. Of which, 26 (22.4%) patients were treated with Dexamethasone and antibiotics and 90(77.6%) were treated with antibiotics only. There was no significant difference between the groups in age, duration of symptoms prior to hospitalization, body temperature or levels of acute phase reactants. Bacteria were isolated from 23 patients (20%) without any difference between the two groups. Patients treated with Dexamethasone had a significantly shorter duration of fever (mean 1 st day without fever 2.3 vs. 3.9) (p = 0.002), shorter duration of parenteral antibiotic treatment (mean of 7.1 vs. 11.4 days) (p < 0.001) and accelerated clinical improvement (mean 1 st day without pain or any limitation in physical examination 6.3 vs. 10 days)(p<0.001). Likewise, C‐reactive protein (CRP) levels declined faster below 1mg/dL in the Dexamethasone group (mean of 5.3 vs. 8.4 days) (p = 0.002) and the hospital stay was significantly shorter (mean of 8 vs. 10.7 days) (p = 0.004). No side effects of treatment were recorded in either group, but in the Dexamethasone group a short rebound of symptoms occurred in 3/26 (11.5%) patients after completing the course of steroids. Conclusion: A short course of Dexamethasone given early, in addition to antibiotics, leads to a significant clinical and laboratory improvement, shortens duration of treatment and accelerates recovery in children with septic arthritis.